2008
DOI: 10.1038/emboj.2008.244
|View full text |Cite
|
Sign up to set email alerts
|

microRNA-122 stimulates translation of hepatitis C virus RNA

Abstract: Hepatitis C virus (HCV) is a positive strand RNA virus that propagates primarily in the liver. We show here that the liver-specific microRNA-122 (miR-122), a member of a class of small cellular RNAs that mediate posttranscriptional gene regulation usually by repressing the translation of mRNAs through interaction with their 3 0 -untranslated regions (UTRs), stimulates the translation of HCV. Sequestration of miR-122 in liver cell lines strongly reduces HCV translation, whereas addition of miR-122 stimulates HC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
526
4
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 598 publications
(553 citation statements)
references
References 42 publications
15
526
4
2
Order By: Relevance
“…Interestingly, expression of miR-122 has been shown to endow the ability of supporting efficient HCV RNA replication and infectious virion production in HepG2 cells (Narbus et al, 2011). Henke et al (2008) further uncovered a unique interaction of miR-122 with two binding sites in the 5′-UTR of the viral genome, which stimulates HCV translation by enhancing the association of ribosomes with the viral RNA. Structure analysis demonstrated that miR-122 triggers an open conformation of the HCV internal ribosome entry site (IRES), which may facilitate HCV translation (Díaz-Toledano et al, 2009).…”
Section: Mir-122 In Hcv Infectionmentioning
confidence: 99%
“…Interestingly, expression of miR-122 has been shown to endow the ability of supporting efficient HCV RNA replication and infectious virion production in HepG2 cells (Narbus et al, 2011). Henke et al (2008) further uncovered a unique interaction of miR-122 with two binding sites in the 5′-UTR of the viral genome, which stimulates HCV translation by enhancing the association of ribosomes with the viral RNA. Structure analysis demonstrated that miR-122 triggers an open conformation of the HCV internal ribosome entry site (IRES), which may facilitate HCV translation (Díaz-Toledano et al, 2009).…”
Section: Mir-122 In Hcv Infectionmentioning
confidence: 99%
“…Although miRNAs are generally known to down-regulate gene expression by inhibiting translation or inducing target mRNA degradation, a growing number of studies have demonstrated that miRNAs can also upregulate the expression of their targets under certain circumstances. 56,57 For example, miR-346 activates the activity of receptor-interacting protein 14 by increasing its protein expression 57 and miR-373 has been reported to target the promoter sequences of E-cadherin and cold-shock domaincontaining protein C2 to induce their expression. 58 Therefore, further experiments are required to determine whether any of these LNA-21-downregulated proteins are direct targets of miR-21.…”
Section: Silencing Of Pias3 Reverses the Effect Of Mir-21 Inhibition mentioning
confidence: 99%
“…Some years ago, the central role of miRNAs in susceptibility to viral infection was described: miRNA-122 expression and hepatitis C virus infection (4), and miRNA-125b and HPV infection in cervical cancer (5).…”
Section: Introductionmentioning
confidence: 99%